2023
DOI: 10.3390/su15032714
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Personalized Precision Education Using the Catboost Model during the COVID-19 Lockdown Period in Pakistan

Abstract: With the emergence of the COVID-19 pandemic, access to physical education on campus became difficult for everyone. Therefore, students and universities have been compelled to transition from in-person to online education. During this pandemic, online education, the use of unfamiliar digital learning tools, the lack of internet access, and the communication barriers between teachers and students made precision education more difficult. Customizing models from previous studies that only consider a single course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The presented model may be used for course recommendation and mapped to a recommendation system issue. Altaf et al [1] presented various distinct models for course performance prediction. The methodology developed in this research is broad enough to produce accurate predictions based on many inputs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented model may be used for course recommendation and mapped to a recommendation system issue. Altaf et al [1] presented various distinct models for course performance prediction. The methodology developed in this research is broad enough to produce accurate predictions based on many inputs.…”
Section: Related Workmentioning
confidence: 99%
“…These platforms offer hundreds of courses to learners. Parallel research results on online education platforms indicate that learners face great difficulty selecting an appropriate course due to the many online course providers and the large set of course data [1].…”
Section: Introductionmentioning
confidence: 99%
“…CatBoost incorporates all the settings needed to build separate decision trees and set up the random forest. The literature [41][42][43] can be referenced for further information about CatBoost.…”
Section: Categorical Boosting (Catboost)mentioning
confidence: 99%
“…How to analyze and mine the massive data of college students' behaviors and habits, and improve the precise education for college students according to their needs is one of the important problems faced by colleges and universities at present [8][9]. Asad, R et al argued that educational data mining can help teachers to better understand students' learning, and for online education, pushing accurate education to students has become the goal to be achieved by popular media education and by comparing five different machine learning methods, it was concluded that the superiority of hybrid integrated learning models in predicting students' learning outcomes [10]. Aykan, E et al took Elsies University of students to investigate the influence of personality traits on innovation and entrepreneurship of university students and concluded that there is a positive correlation between personality traits and sub-dimensions and entrepreneurial intentions, while learning is one of the most important factors affecting the personality traits of students [11].…”
Section: Introductionmentioning
confidence: 99%